2018
DOI: 10.1111/1753-6405.12730
|View full text |Cite
|
Sign up to set email alerts
|

Surveying all public drinking water fountains in a city: outdoor field observations and Google Street View

Abstract: Objective: Drinking fountains are a public amenity that may help counter the obesogenic environment (sugary beverages) and reduce the risk of heat stroke during heat waves. As a case study, we aimed to survey all public fountains in a city: Wellington, New Zealand, and to determine the utility of Google Street View in studying drinking fountains. Methods:Using a sample of all public drinking fountains in a City Council map, a field observer assessed their exact location and tap functionality, and photographed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study that surveyed public drinking fountains reported that 46.7% (21/45) of the drinking fountain had discoloration around the faucet's spout and the presence of some algae growth suggesting the need for improvements physical structure and cleaning of drinking fountains 24 . A survey conducted in California revealed that 90% of the drinking fountains analyzed were fully operational.…”
Section: Discussionmentioning
confidence: 99%
“…A study that surveyed public drinking fountains reported that 46.7% (21/45) of the drinking fountain had discoloration around the faucet's spout and the presence of some algae growth suggesting the need for improvements physical structure and cleaning of drinking fountains 24 . A survey conducted in California revealed that 90% of the drinking fountains analyzed were fully operational.…”
Section: Discussionmentioning
confidence: 99%